Growth, oil and protein yield of Jatropha curcas L. populations - Silva, Djair Felix; Dias, Luiz Antônio Santos; Neves, Júlio César Lima; Matos, Fábio Santos (Acta Iguazu, 2021)
Jatropha curcas L. is an oilseed with multiple applications, especially the pharmaceutical-industrial one. Cultivation is still very low due to the lack of commercial varieties, therefore, with the need to start the genetic improvement program and select superior genotypes, it is essential to know the genetic variability of the culture. Thus, the purpose of this study was to evaluate the vegetative growth, grain yield and oil and protein content in seeds populations of Jatropha curcas, to support the species breeding program. The experiment was carried out at the University Federal de Viçosa, State of Minas Gerais, Brazil, using a randomized complete block split-plot design with four replications and 4-plant plots, spaced at 2.5 m. Each plot consisted of clones of six populations coming from the towns of Janaúba (J1, J2, J3, J4 and J5) and Bonfim (B1), located in Minas Gerais. The 4.5-year-old populations were evaluated for plant height, stem diameter, leaf and fruit dry matter, grain yield and oil and protein content. The populations presented different plant heights (2.97 m), stem diameters (13.49 cm) and leaf dry matter (0.818 g) amounts. The J5 population showed taller plants (3.29 m) with longer stem diameter (15.34 cm). The greatest dry leaf weight (0.864 g leaf-1) was observed in the J2 population. The populations did not present genetic variability for fruit dry matter, grain yield and oil and protein content. Overall, the J5 population stood out with the highest levels of growth, grain yield and seed oil (31.7%) content.